Pengaruh Keterampilan Berwirausaha terhadap Minat Berwirausaha melalui Sikap Berwirausaha dan Perceived Behavior Control Pada Santri di Pondok Pesantren Kabupaten Kediri - Rina Indra Sabella; Rudiana Fibriani; Siti Masruroh (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2022)
This study analyzes the Entrepreneurial Interest of Islamic Boarding School students in Kediri by using the Theory of Planned Behavior. Santri, as they are called, lack a positive image in the business world. Therefore, this study discusses the Entrepreneurial Interest of Santri. By using the variables of Entrepreneurial Skills, Entrepreneurial Attitudes, and Perceived Behavior Control. This research is a quantitative research with an explanatory research approach. The data were taken from the Lirboyo, Darussalam, Al Falah, and Darul Ulum Islamic Boarding Schools in Kediri with a total sample of 104 university students. Data analysis in this study used the Partial Least Square (PLS) method. The results of this study are, Entrepreneurship Skills contribute to Interest in Entrepreneurship, Entrepreneurship Skills contribute to Interest in Entrepreneurship through Attitudes, and Entrepreneurship Skills contribute to Interest in Entrepreneurship through Perceived Behavior Control